Quality indicators of colorectal cancer care in southern Switzerland: results from a population-based study (Swiss Medical Weekly, 2017)
AIM OF THE STUDY Assessing the quality of cancer care (QoCC) has become increasingly relevant to providers, regulators and purchasers of healthcare worldwide. The aim of this study was to assess adherence to validated quality indicators (QIs) for colorectal cancer (CRC) in a population-based setting, and to compare results with the available literature. METHODS All colorectal cancers diagnosed between 1 January 2011 and 31 December 2012 were identified from the files of the population-based Ticino Cancer Registry, southern Switzerland. We computed 12 core QIs, approved by use of the validated Delphi methodology and for which all the necessary medical documentation was available or only minor data collection was still needed to complete the analysis: three for diagnosis, two for pathology and seven for treatment (surgery, oncology and radiotherapy). Each QI was analysed as proportion (%) with 95% confidence interval, following the approach “available case analysis”. RESULTS A total of 474 colorectal cancers were identified: 86.9% patients were diagnosed after they reported symptoms, 90.2% had preoperative colonoscopy, 8.7% underwent emergency surgery, 97.2% had a surgical resection with tumour-free margins, and for 86.6% at least 12 lymph nodes were examined. The overall 30-day postoperative mortality was 3.6% and 66.7% of locally advanced rectal cancers benefited of neoadjuvant radiotherapy ± chemotherapy. CONCLUSIONS Our study showed the feasibility of assessing QoCC using Cancer Registry population-based data. Results according to the clinical domain of pathology, surgery, oncology and radio-oncology in southern Switzerland are generally positive and encouraging, sometimes more favourable in comparison with other international studies, except the very low proportion of patients with a diagnosis based on opportunistic screening (8.6%). Considering the lack in the literature of population-based studies, further national and international reports are urgently needed for comparative analysis as well as standardisation of QI definition is absolutely necessary for inter-regional comparative goals.